Pembinaan laman web sebagai bahan rujukan pembelajaran pelajar Sarjana Pendidikan Teknik dan Vokasional, Kolej Universiti Teknologi Tun Hussein Onn - Stapah@Salleh, Mazura (2001)
Web site had become one of the main Educational Teaching Supporting Tools (ABBM) in our country. However, it is found that Master in Educational students (MID) of Kolej Teknologi Tun Hussein Onn (KUiTTHO) do not have adequate skills in developing web site. Thus, the study was carried out in order to produce "Manual Asas Pembinaan Laman Web" (MAPLW). 126 of 3 rd semester MTD students at KUiTTHO had become the sample of this study. Survey techniques was used to obtained feedback from MTD students whether the information in MAPL W is adequate in helping them to build web site. The study also try to find out whether the manual is 'user friendly' from the aspect of the learning content, illustration anq writing. Data was analyzed using Statistical Package for Social Science ]0.0 for Windows (SPSS 10.0). The result shows that the information in MAPL W was adequately as a learning reference for MTD students. The researcher also found that the manual is 'user friendly' from the aspect of learning content, illustration used and writing.